>> General Intellingence and Reasoning >> Statements(Mathematical) and Conclusions

PrimeFaces.cw("DataGrid","widget_frm_base_j_idt45",{id:"frm_base:j_idt45"});

Contents:

- General Intellingence and Reasoning
- Analogy
- Classification
- Coding and Decoding
- Input Rearrangement
- Numerical Operations
- Questions based on Codes
- Questions based on Information(Bank Exams)
- Relationship
- Relationship in Equations
- Seating Arrangement
- Seating Arrangement(Circular)
- Series
- Statements and conclusions
- Statements(Mathematical) and Conclusions

II. \( y^{2} - 24y + 144 = 0 \)
I. \( \large x^{2} = 144 \) =>\( \large x = \sqrt{144} = \pm 12 \) II. \( \large y^{2} - 24y + 144 = 0 \) \( \large y^{2} - 12y-12y + 144 = 0 \) \( \large y (y - 12) - 12 (y - 12) = 0 \) \( \large (y - 12) (y - 12) = 0 \) Y = 12 So. \( \large x \le y \) | ||||||

2). I.\( 2x^{2} - 9x +10 = 0 \) II. \( 2y^{2} - 13y +20 = 0 \)
\( \large 2x^{2} - 9x +10 = 0 \) \( \large 2x^{2} - 5x - 4x +10 = 0 \) \( \large x(2x - 5) - 2(2x +5) = 0 \) \( \large(2x - 5) - (x -2) = 0 \) \( \large x = \frac{5}{2},4 \) \( \large x \le y \) | ||||||

3). I.\( 2x^{2} + 15x +27 = 0 \) II. \( 2y^{2} + 7y +6 = 0 \)
I. \( \large 2x^{2} + 15x + 27 = 0 \) \( \large 2x^{2} + 9x + 6x + 27 = 0 \) \( \largex( 2x + 9) + 3(2x + 9)= 0 \) \( \large (x + 3)(2x + 9) = 0 \) \( \large x = -\frac{9}{2},-3 \) II. \( \large 2y^{2} + 7y + 6 = 0 \) \( \large 2y^{2} + 4y + 3y + 6 = 0 \) \( \large 2y( y + 2) + 3(y + 2) = 0 \) \( \large (y + 2)( 2y + 3) = 0 \) \( \large y = -2, - \frac{3}{2} \) So x < y | ||||||

4). I.\( 3x^{2} - 13x +12 = 0 \) II. \( 3y^{2} - 13y +14 = 0 \)
I. \( \large 3x^{2} - 13x +12 = 0 \) \( \large 3x^{2} - 9x - 4x +12 = 0 \) \( \large 3x(x - 3) - 4(x - 3) = 0 \) \( \large (x - 3)(3x - 4) = 0 \) X = \( \large \frac{4}{3},3 \) II. \( \large 3y^{2} - 13y + 14 = 0 \) \( \large 3y^{2} - 7y - 6y + 14 =0 \) \( \large y(3y - 7) - 2(3y - 7) = 0 \) \( \large(3y - 7)(y-2) = 0 \) \( \large y = 2,\frac{7}{3} \) Relationship cannot be established. | ||||||

5). I.\( 5x^{2} + 8x +3 = 0 \) II. \( 3y^{2} + 7y +4 = 0 \)
I. \( \large 5x^{2} + 8x + 3 = 0 \) \( \large 5x^{2} + 5x + 3x + 3 = 0 \) \( \large 5x(x + 1) + 3(x + 1) = 0 \) \( \large(x + 1)(5x + 3)= 0 \) \( \large x = -1,- \frac{3}{5} \) II. \( \large 3y^{2} + 7y + 4 = 0\) \( \large 3y^{2} + 4y + 3y + 4 = 0\) \( \large y(3y + 4) + 1(3y + 4) = 0\) \( \large (3y + 4) (y+ 1) = 0 \) \( \large y = -\frac{4}{3}, -1 \) So \( \large x \ge y \) | ||||||

415 764 327 542 256 What will be the resultant if second digit of the lowest number and third digit of the highest number are multiplied?
415 764 327 542 256 The lowest number = 256 It's second digit = 5 The highest number = 764 It's third digit = 4 Required product = \( 5 \times 4 = 20 \) | ||||||

7). If '1' is added to the first digit of every odd number and '2' is subtracted from the second digit of every even number, in how many numbers will a digit appear twice?
Correct Answer: Three
415 --- 515 764 --- 744 327 --- 427 542 --- 522 256 --- 236 | ||||||

8). The positions of the first and the second digits of each of the numbers are interchanged. What will be the resultant if third digit of highest number thus formed is divided by the second digit of the lowest number thus formed?
415 --- 145 764 --- 674 327 --- 237 542 --- 452 256 --- 526 The highest number = 674 It's third digit = 4 The lowest number = 145 It's secondf digit = 4 Required resultant = \( \frac{4}{4} = 1 \) | ||||||

9). If in each number all the digits are arranged in ascending order from left to right within the number, how many numbers thus formed will be odd numbers?
Correct Answer: Four
415 --- 145 764 --- 467 327 --- 237 542 --- 245 256 --- 256 | ||||||

10). If all the numbers are arranged in ascending order from left to right, which of the following will be the sum of all the three digits of the number which is third from the left?
\( 256 < 327 < 415 < 542 < 764 \) Third number from left = 415 Required sum = \( 4+1+5 = 10 \) |